Groundwork, Fieldwork and Transnational Research - Christians and Jews in Ethiopia - Kaplan, Steven (Entangled Religions, 2018)
This paper gives a short overview of the current state of research of the study of Beta Israel history, including a response to two papers in this volume by Dege-Müller and Kribus and Krebs that deal with various Beta Israel sources.